Rethinking the African language curriculum (with special reference to SiSwati) : a theoretical and empirical study - Mahlalela, Babazile (School of Education, 2014)
The field study based on a questionnaire, classroom observation and a range of interviews with government officials and teachers confirmed a deeply negative attitude towards the way SiSwati is being taught, resulting in negative attitudes towards the language itself. Other findings pointed to a resistance to the cultural content of the curriculum as dictated by the power elite in Swaziland, the outdated emphasis on linguistics rather than sociolinguistics as an informing discipline and the absence of social and negative literacy skills embedded in subject content. The field study reflects an overall climate of despondency governing the teaching and learning context.